Climate change and fossil fuel production cuts: assessing global supply-side constraints and policy implications. (13th September 2020) - Gaulin, Nicolas; Le Billon, Philippe
ABSTRACT: This paper presents the first global database of supply-side climate initiatives seeking to constrain fossil fuel production. There is a clear imperative to keep a large proportion of fossil fuel reserves underground to keep global temperature rise under 2°C above pre-industrial levels. Yet, there is no global overview of supply-side initiatives taken to constrain fossil fuel production, making it difficult to track trends, compare efforts across countries, and assess the effectiveness of different supply-side approaches. The Fossil Fuel Cuts Database presented here identifies 1302 initiatives implemented between 1988 and 2017 in 106 countries across the seven major types of supply-side approaches. Documenting temporal and geographical patterns, we show a rapid growth in the number of supply-side initiatives taken during the past decade and their highly uneven adoption across the world. Most initiatives occurred in countries with low economic dependence on fossil fuel production and limited fossil fuel exports, with the partial exception of Canada and Norway at the national level, and the US at the sub-national level. We discuss policy implications and the need for further research to identify adoption factors, effectiveness, and policy implications. The documentation of a wide range of supply-side initiatives serves as a reminder that constraints on fossil fuel production need to be analysed and considered on a par with demand-side interventions, including in Assessment Reports of the Intergovernmental Panel on Climate Change (IPCC). Key policy insights Supply-side constraint initiatives have increased in the past decade, suggesting growing policy take-up and potential mitigation impacts. Supply-side initiatives clearly emphasize the key role and responsibility of major carbon producers, and help mobilize demand for greater accountability. Supply-side initiatives take many forms and can suit the capabilities of different actors, from civil society organizations to governments. Supply-side initiatives can usefully complement demand-side measures and help tackle free-rider problems. Larger coalitions of fossil fuel producers are required to address uneven adoption, prevent the relocation of production, and help producers transition away from fossil fuels.